PERAN PENYULUH PERTANIAN DALAM UPAYA PENINGKATAN PRODUKSI KACANG TANAH STUDI KASUS DI DESA GUNUNG SARI KECAMATAN GUNUNG SARI KABUPATEN LOMBOK BARAT - MADE SUMA WEDASTRA (GANEC SWARA, 2023)
Peanut production in Gunung Sari Village is still low when compared to production in West Lombok Regency. The existence of a touch of technology in the adoption of peanut farming technology does not necessarily increase production. For this reason, it is necessary to increase farmer resources through the role of extension workers in the development of peanut farming. The research conducted in Gunung Sari Village from February to April 2023, aims to determine the role of agricultural extension workers in efforts to increase peanut production in Gunung Sari Village, Gunung Sari District, West Lombok Regency.         The number of respondents used was 24 people, which was carried out by census, where the entire population was taken as a sample. Data analysis used a Likert scale and then analyzed the role of extension workers based on 9 categories, namely: motivator, educator, catalyst, organizer, communicator, counselor, adviser, facilitator and evaluator.          Based on descriptive analysis, with role analysis, it can be said that extension workers have played a role in increasing peanut production in Gunungsari Village, Gunungsari District, West Lombok Regency, with an average score of 65.89. Thus the extension worker plays a role as a motivator, educator, catalyst, communicator, counselor, facilitator, organizer, adviser and evaluator.